2011
DOI: 10.1002/dev.20572
|View full text |Cite
|
Sign up to set email alerts
|

Handedness for grasping objects and declarative pointing: A longitudinal study

Abstract: It is still unclear whether infants become right-handed because of their left-hemisphere specialization for language (through gestural communication for instance), whether they speak predominantly with their left hemisphere because of this hemisphere's superiority in controlling sequential actions which first results in right-handedness, or whether the two lateralization processes develop independently. To tackle this question, we followed 26 human infants from 8 to 20 months to evaluate the temporal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 70 publications
(79 reference statements)
6
61
2
1
Order By: Relevance
“…Not surprisingly, vision also plays a critical role in hand preference for grasping. During visually-guided grasping tasks, individuals (even some left-handed) exhibit a clear preference to grasp objects with the right-hand (Bishop, Ross, Daniels & Bright, 1996;Calvert & Bishop, 1998;Gabbard & Rabb, 2000;Gonzalez & Goodale, 2009;Jacquet, Esseily, Rider & Fagard, 2012;Stone & Gonzalez, 2014a;Stone, Bryant & Gonzalez, 2013). The role of haptics in hand preference for grasping however, has been seldom investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Not surprisingly, vision also plays a critical role in hand preference for grasping. During visually-guided grasping tasks, individuals (even some left-handed) exhibit a clear preference to grasp objects with the right-hand (Bishop, Ross, Daniels & Bright, 1996;Calvert & Bishop, 1998;Gabbard & Rabb, 2000;Gonzalez & Goodale, 2009;Jacquet, Esseily, Rider & Fagard, 2012;Stone & Gonzalez, 2014a;Stone, Bryant & Gonzalez, 2013). The role of haptics in hand preference for grasping however, has been seldom investigated.…”
Section: Introductionmentioning
confidence: 97%
“…communicative and non-communicative) have not been previously shown to be correlated in young children [e.g. 17,49,[52][53][54]. In fact, a disparate range of experimental paradigms for assessing handedness in children has resulted in a variety of patterns of asymmetries depending hand action function [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that mothers deliberately train their infants to use a particular hand. However, during play it is conceivable that the mother’s own handedness may bias the infant’s hand-use (e.g., placing objects near the infant’s right hand) and activate the ipsilateral hand as we have seen (Fagard et al, 2009; Suzuki et al, 2009; Jacquet et al, 2012). Additionally, Michel (1992) has shown that infants match maternal hand-use and that this matching increases with age.…”
Section: Discussionmentioning
confidence: 80%
“…This manual preference is quantified in terms of speed and/or performance, and scores of handedness can vary depending on the specificity of the task considered (Fagard and Marks, 2000). For example, symbolic gestures such as signing or pointing – which appear in the second year of life during the period of linguistic explosion – elicit a stronger degree of predominance of right-handedness than non-communicative manual actions in young children (Bates et al, 1986; Vauclair and Imbault, 2009; Cochet and Vauclair, 2010b; Jacquet et al, 2012). Studies on handedness are organized around two axes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation